Distributed Computing 22nd International Symposium, DISC 2008, Arcachon, France, September 22-24, 2008, Proceedings - Taubenfeld, Gadi (Theoretical Computer Science and General Issues, 2008)
This book constitutes the refereed proceedings of the 22nd International Symposium on Distributed Computing, DISC 2008, held in Arcachon, France, in September 2008. The 33 revised full papers, selected from 101 submissions, are presented together with 11 brief announcements of ongoing works; all of them were carefully reviewed and selected for inclusion in the book. The papers address all aspects of distributed computing, including the theory, design, implementation and applications of distributed algorithms, systems and networks - ranging from foundational and theoretical topics to algorithms and systems issues and to applications in various fields.